Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Pada Toko Buku Aziz Samarinda - Tagfirul Azima Yoga Siswa, Muspidar Mulyadi (EKONOMIA, 2021)
The purpose of this study is: 1.) To find out the effect of the Product on purchasing decisions at Aziz’s Bookstore Samarinda. 2.) To find out the effect of Price on purchasing decisions at Aziz’s Bookstore Samarinda 3.) To find out the effect of Location on Purchasing Decisions at Aziz’s Bookstore Samarinda. 4.) To find out the effect of Promotion on Purchasing Decisions at Aziz’s Bookstore Samarinda. 5.) To find out the effect of Product, price, location, and promotion together with the Purchasing Decision at Aziz’s Bookstore Samarinda.This study was done at Aziz’s bookstore on Aga Khan Street (Citra Niaga Lounge) Samarinda. The sample used in this study were 100 respondents with a Probability Sampling Method and the technique sampling is Simple Random Sampling. Data was collected by distributing questionnaires and using likert scale for each indicator. The Analytical tool used is Multiple Linear Regression at SPSS V23 Programm. The results of this study shows : 1.) Product variable did not significantly influence of purchasing decisions at Aziz’s Bookstore Samarinda. 2.) Price variable did not significantly influence of purchasing decisions at Aziz’s Bookstore Samarinda. 3.) Place variable did significantly influence of purchasing decisions at Aziz’s Bookstore Samarinda. 4.) Promotion variable did not significantly influence of purchasing decisions at Aziz’s Bookstore Samarinda. 5.) The variables of Product, price, location, and promotion together significant effect on purchasing decisions at Aziz’s Samrinda Bookstore.